PENERAPAN MANAJEMEN KATERING BERBASIS STANDAR HIGIENE DAN SANITASI DALAM PROGRAM PENDIDIKAN TINGGI VOKASI DI BIDANG JASA BOGA DI KOTA BANDUNG - Andriyono, Toni (Jurnal Perhotelan dan Pariwisata, 2025)
The implementation of hygiene and sanitation standards in catering management is a crucial aspect of the food service industry, especially in vocational education settings that prepare professional workers. This study aims to analyze the implementation of hygiene and sanitation standards in higher vocational education programs in the culinary field in Bandung. The research employs an observational study and policy analysis across several vocational education institutions with culinary programs. The findings indicate that most institutions have implemented hygiene and sanitation standards in accordance with existing regulations, although challenges remain in monitoring and student compliance. This study recommends enhancing training, stricter monitoring, and integrating a more comprehensive practice-based curriculum to improve awareness and adherence to hygiene and sanitation standards.